The Determinants of Corporate Hedging with Derivatives in UK Non-Financial Companies - Yan, Shimeng (2019)
This study empirically investigates the determinants of corporate hedging with derivatives in UK non-financial companies. Based on previous researches and evidences, this study examines seven potential determinants on the decision of firms undertaking hedging activities, which contains financial distress cost, underinvestment, scale economies, foreign exposure, hedging substitutes, managerial risk aversion and tax incentives. Moreover, the sample of this study consists of 400 UK firms with different firm sizes and industries, and the hedging data are manually collected from corporate annual reports from fiscal year 2017 to 2018, while financial data are directly download from Bloomberg. Through adopting Mean difference test, Wilcoxon rank sum test, a combination of Univariate and Multivariate logit regressions and Robustness check, this study suggests that financial distress cost, scale economies and foreign exposure are positively related with the probability of corporate hedging, while there is a significantly negative relationship between corporate hedging decision and underinvestment or hedging substitutes in UK non-financial firms.